Sexuality Education and New Materialism Queer Things - Allen, Louisa (Queer Studies and Education, 2018)
This book aims to explore what queer thinking and new materialist feminist thought might offer the field of sexuality education. It argues that queer theory in education might be queered further by drawing on feminist new materialism and extending itself to subjects beyond sexual and gender identities/issues, including a focus on 'things'. Allen explores how new materialism as a form of queer thinking, might be brought to bear on other important issues of social justice such as, classroom cultural and religious diversity.